Concern and fear of covid-19 in Peruvian nurses working in emergency services, 2021 : Preocupación y miedo al covid-19 en enfermeros peruanos que laboran en servicios de emergencia, 2021 - MAMANI, GABINA (2024)
Introduction: There are few studies that evaluate the worry and fear of covid-19 in healthcare professionals who work in emergency services in low- and middle-income countries. Objective: To characterize the concern for contagion and fear of covid-19 in Peruvian nurses who work in emergency services. Materials and methods: Comparative descriptive, correlational and cross-sectional study. 212 nurses were surveyed in 2021. The correlation coefficient of Pearson and ANOVA test were used. Results: Regarding concern, 41% often think about the probability of getting infected, 45.3% consider that it affected their state of mind, but 82.5% estimated that they had not affected their work abilities. On the other hand, 34.4% strongly agree that they are very afraid and 35.3% are very afraid of losing their lives. In addition, the comparative analysis by item reported that women, those who do face-to-face work, and those who had not received vaccinations show a lower frequency in some items of concern; while men, who do face-to-face work and who have only one dose of the vaccine, have a higher frequency in the fear items. Discussion: The results refer us to a problem little studied in Latin America and makes it possible to understand that nurses are emotionally affected by sanitary conditions. Conclusions: The nurses who work in the emergency services present a medium level of both concern about contagion and fear of COVID-19.